2021
DOI: 10.1038/s41598-021-87873-w
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of zona incerta selectively modulates pain in humans

Abstract: Stimulation of zona incerta in rodent models has been shown to modulate behavioral reactions to noxious stimuli. Sensory changes observed in Parkinsonian patients with subthalamic deep brain stimulation suggest that this effect is translatable to humans. Here, we utilized the serendipitous placement of subthalamic deep brain stimulation leads in 6 + 5 Parkinsonian patients to directly investigate the effects of zona incerta stimulation on human pain perception. We found that stimulation at 20 Hz, the physiolog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
(11 reference statements)
0
10
0
1
Order By: Relevance
“…Similarly, the DMH, which our data show synapses directly on AVP + PVN neurons, has been linked to modulation of pain with acute stress suppressing pain and chronic stress increasing pain sensitivity (Freitas et al., 2009). Studies that inactivate the DMH in conjunction with mild stressors block the sensitivity to mechanical stimulation, while activation increases pain sensitivity, confirming that the DMH mediates behavioral hyperalgesia (Wagner et al., 2013), and direct activation of the ZI modulates behavioral responses to noxious stimuli (Lu et al., 2021). Central pain syndrome, a condition resulting from dysfunction in the spinal cord, has been associated with abnormal regulation of the posterior thalamus by way of signaling from the ZI (Masri et al., 2009).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, the DMH, which our data show synapses directly on AVP + PVN neurons, has been linked to modulation of pain with acute stress suppressing pain and chronic stress increasing pain sensitivity (Freitas et al., 2009). Studies that inactivate the DMH in conjunction with mild stressors block the sensitivity to mechanical stimulation, while activation increases pain sensitivity, confirming that the DMH mediates behavioral hyperalgesia (Wagner et al., 2013), and direct activation of the ZI modulates behavioral responses to noxious stimuli (Lu et al., 2021). Central pain syndrome, a condition resulting from dysfunction in the spinal cord, has been associated with abnormal regulation of the posterior thalamus by way of signaling from the ZI (Masri et al., 2009).…”
Section: Discussionmentioning
confidence: 85%
“…The BNST, which provided the strongest input from the pallidum, is, similarly, linked to anxiety‐like behaviors in humans (Avery et al., 2016) and animals (Ch'ng et al., 2018; Harris et al., 2018), which can be sex specific (Luo et al., 2021). Thus, we identified significant input likely linked to the regulation and response to stress (Chou et al., 2018; Dinan & Scott, 2005; Ferris, 2000; Inutsuka et al., 2016; Lu et al., 2021; Masri et al., 2009) and to changing internal and environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Deep brain stimulation of ZI has been demonstrated to improve akinesia and bradykinesia in patients with Parkinson's disease (Voges et al, 2002), proximal tremor in patients with multiple sclerosis (Nandi et al, 2002), as well as obsessive symptoms in patients with obsessive compulsive disorder (Mallet et al, 2002). Interestingly, Lu et al (2021) noticed changes of human perception of experimental heat pain in subthalamic DBS patients, supporting ZI as a potential target for pain modulation. Herein, we showed that ZI PV neurons negatively regulate scratching behaviors evoked by chronic itch.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the activities of GABAergic neurons within ZI were decreased in chronic pain rodents compared with the sham-treated group [ 10 , 11 , 12 ]. On the other hand, the ZI deep brain stimulation with 20 Hz decreased pain in humans [ 13 ]. These reports indicate that as a key nucleus, ZI might be involved in the pain neurotransmission and modulation.…”
Section: Introductionmentioning
confidence: 99%